The Effect of Divorce Law Implementation and Access to Economic Resources on Women's Economic Independence in Blitar Regency - Tertibi, Yaoma; Gleydis Harwida; Evita Novilia; Akhzalini, Hana Athia (International Journal of Integrative Sciences, 2024)
This study aims to analyze the effect of divorce law implementation and access to economic resources on women's economic independence in Blitar Regency. This study uses a quantitative method with a survey approach and multiple linear regression analysis to determine the relationship between the variables studied. The results showed that both the implementation of divorce law and access to economic resources have a significant influence on women's economic independence. These findings indicate the importance of policies that support women's economic empowerment after divorce, as well as the need to increase access to economic resources such as skills training, access to credit, and social support to increase women's economic independence.